Assessing Paleoclimate through Major and Trace Element Concentrations: A Review - Osama Shaltami,; Mustafa Ben Hkoma, (AlQalam Journal of Medical and Applied Sciences, 2024)
In geoscience, it is possible to deduce the paleoclimate of sediments from their lithology, fossil content, chemical composition, or geophysical characteristics. In this paper, the author reviewed the use of the concentration of major and trace elements to infer the paleoclimate. For this purpose, a variety of markers have been used in the previous studies, such as CIA, C.I, K2O/Al2O3, Al/Mg, Mg/Ca, Fe/Mn, Rb/Sr, Sr/Cu, Ga/Rb, Sr/Ba, ΣREE, and Eu anomaly. It should be noted that, for a more accurate evaluation of paleoclimate, discrimination diagrams (the plots of K2O+Na2O+Al2O3 versus SiO2, CIA versus C.I, K2O/Al2O3 versus Ga/Rb, Fe/Mn versus Sr/Ba, Rb/Sr versus Sr/Cu, and Mg/Ca-Al/Mg-ΣREE) are the recommended technique في علم الأرض، من الممكن استنتاج المناخ القديم للرواسب من خلال خصائصها الصخرية أو محتواها الأحفوري أو تركيبها الكيميائي أو خصائصها الجيوفيزيائية. في هذه الورقة، استعرض المؤلف استخدام تركيز العناصر الرئيسية والعناصر النزرة لاستنتاج المناخ القديم. لهذا الغرض، تم استخدام مجموعة متنوعة من العلامات في الدراسات السابقة، مثل CIA وC.I وK2O/Al2O3 وAl/Mg وMg/Ca وFe/Mn وRb/Sr وSr/Cu وGa/Rb وSr/Ba وΣREE وشذوذ Eu. تجدر الإشارة إلى أنه من أجل تقييم أكثر دقة للمناخ القديم، فإن مخططات التمييز (مخططات K2O+Na2O+Al2O3 مقابل SiO2، وCIA مقابل C.I، وK2O/Al2O3 مقابل Ga/Rb، وFe/Mn مقابل Sr/Ba، وRb/Sr مقابل Sr/Cu، وMg/Ca-Al/Mg-ΣREE) هي التقنية الموصى به